An exploratory study of understanding project risk management from the perspective of national culture. Issue 3 (April 2015) - Liu, Junying; Meng, Fanye; Fellows, Richard
Abstract Cultural influence is unavoidable in construction projects and a clear understanding of it is vital for successful risk management. This study aims to explore how culture influences contractors' risk management. A case study method is selected including four projects in China, Poland and Singapore. Data are collected through interviews and archival documents. Major risks are identified and risk management in each case is discussed in the context of Hofstede's theory. A conceptual framework is proposed to reveal the link between culture and risk management. The findings show that project risks are perceived and managed differently in different national cultures. It is indicated that IDV and UAI are the foci of attention, beyond the contributions of PDI, LTO and MAS, and that contractors' knowledge of the host country's national culture influences their risk management behaviors. Having such information is of great importance to improve international contractors' risk management practice.